1989
DOI: 10.1084/jem.169.6.1961
|View full text |Cite
|
Sign up to set email alerts
|

Clonal analysis of cytotoxic and regulatory T cell responses against human melanoma.

Abstract: Studies of T cell-mediated immune response against spontaneously arising autologous human tumors have been markedly facilitated by functional analyses of T cells at the clonal level (1-7). This particular approach has now provided a strong support for the long-held belief by some, although viewed skeptically by others, that T cell-mediated host responses do indeed exist in different types ofhuman cancers. The evidence for such T cell antitumor response has been particularly impressive in malignant melanoma (1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 29 publications
(27 reference statements)
1
48
0
Order By: Relevance
“…Treg cells are known to suppress T-cell function (10,16,17) and are reported to be elevated in mRCC patients (34, 35). Four-color analysis of PBMC from patients in this study (n = 34) confirmed that mRCC patients have elevated levels of CD3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treg cells are known to suppress T-cell function (10,16,17) and are reported to be elevated in mRCC patients (34, 35). Four-color analysis of PBMC from patients in this study (n = 34) confirmed that mRCC patients have elevated levels of CD3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of Treg cells is elevated in tumor sites and/or the peripheral blood of patients with advanced tumors (11 -15). Treg cells can impair induction of both antigen-specific and nonspecific T cells in melanoma patients (16,17) and predict reduced survival in multiple cancer cell types (13, 18 -20). Relevant to therapy, experimental models have shown that removal of Treg cells modifies the immune response to tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In malignant melanoma, it has been shown that TIL are able to recognize tumour-associated antigens, and in some cases to lyse the malignant cells [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. These findings provided a basis for the use of in vitro cultured TIL in adoptive immunotherapy in an effort to enhance the in vivo accumulation of tumour-lytic lymphocytes [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…Cells were harvested in a Titertek semi-automatic cell harvester (Skattron, Sterling, VA, USA) and thymidine incorporation was estimated by a Beckman liquid scintillation counter (Beckman Instruments, Irvine, CA, USA). 6 …”
Section: Proliferation Of Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%